Rural ageing : A good place to grow old? - Keating, Norah Christine (Book collections on Project MUSE., 2008)
This important book addresses a growing international interest in 'age-friendly' communities, examining the conflicting stereotypes of rural communities as either idyllic and supportive or isolated and bereft of services.